The Seismic Structure of Wilkes Land/Terre Adelie, East Antarctica and Comparison with Australia: First Steps in Reconstructing the Deep Lithosphere of Gondwana - Anya Reading (2004)
A determination of the seismic structure of the crust and uppermost mantle of East Antarctica, in the region of Casey station, Wilkes Land and Dumont D'Urville station, Terre Adelie is presented. High-fidelity waveforms from teleseismic earthquakes recorded at stations CASY and DRV (1996-2001) are used to calculate the seismic receiver function, the signal produced as energy passes through layers in the seismic velocity structure under the receiving station. The receiver functions are stacked to improve the signal-to-noise ratio and then modelled using an inverse algorithm to find the structure that best fits the observed waveform at each station. Inferences are made regarding the tectonic structure, in particular, the crustal thickness and character of the seismic Moho. The crustal thickness under Casey Station is found to be 30 km (+/- 2 km) with a fairly sharp Moho, considerably less than Dumont D'Urville Station, where the crustal thickness is 42 km, and there is a significant low velocity region in the deep crust. The structure of the Wilkes Land lithosphere is comparable to that of the Albany-Fraser Orogen, Western Australia, part of its conjugate margin. This places a new constraint on the relative position of East Antarctica and Australia in the reconstruction of Gondwana, and earlier, supercontinents. A recent reinterpretation of Antarctic geology proposes tectonic province boundaries trending perpendicular to the coast with counterparts in southern Australia. Seismic techniques, determining structure beneath regions with no surface exposure, are vital tools in testing such tectonic hypotheses, towards the reconstruction of Gondwana to full lithospheric depth.